PERAN DUTA WISATA SEBAGAI BRAND AMBASSADOR PARIWISATA KABUPATEN DEMAK - Rosana, Anita Septiani; Kusumawati, Dyah (Jurnal Akuntansi dan Bisnis, 2024)
ABSTRACTIn the tourism context, tourism ambassadors can act as regional brand ambassadors. A brand ambassador is someone appointed by a company or organization to promote a product or service. In this case, tourism ambassadors are appointed by the regional government of Demak Regency to promote tourism potential in Demak Regency. This study's goal is to define the role and duties of tourism ambassadors as brand ambassadors in promoting tourism potential in Demak Regency because brand ambassadors are cultural identities or icons, where they can act as a marketing tool that will represent the product they offer.This study's research object is a qualitative descriptive study being the Demak Tourism Office and tourist attraction managers. The sampling strategy employed in this study a snowballing sample technique, consisting of 7 sources (informants), namely 5 people from the Demak Regency Tourism Office and 2 managers from tourist attractions.The study's conclusions include: (1). The formation of the Demak Tourism Ambassador as a brand ambassador will be able to build and advance all tourism potential in Demak Regency; (2). Demak Tourism Ambassadors have carried out outreach and education activities about Demak tourism, namely by participating in tourism awareness groups (pokdarwis); (3). The Demak Tourism Ambassadors formed the Paguyuban Mas dan Mbak Demak (PAMADE), which aims to be a communication and education forum about Demak tourism. Demak Tourism Ambassadors must have a sense of "sense of belonging" to Demak Regency, especially regarding the world of Demak tourism. The activities carried out are positive and creative to participate in supporting the programs of the Demak Tourism Office. Keywords: tourism ambassador, brand ambassador, tourism